A functionalized renewable carbon-based surface for sensor development - Silva, Martin K. L. [UNESP]; Leão, Alcides L. [UNESP]; Sain, Mohini; Cesarino, Ivana [UNESP] (Springer Nature, 2021)
This paper describes the surface modification of glassy carbon (GC) electrodes with a bamboo-based renewable carbon (RC) before and after an acid functionalization procedure with a sulfonitric solution (1:3 HNO3/H2SO4). The morphology and structural characterization indicate an increase of functional groups in the functionalized renewable carbon (RCF) surface. The enhanced electroanalytical properties of RC and RCF were evaluated by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) in two different setups, in the presence of the redox couple ([Fe(CN)6]3−/4−) and escitalopram (EST). The results revealed an enhancement for the electrochemical responses of both inorganic and organic compounds in the electrolyte. Therefore, the use of new carbon-based materials such as renewable carbon for development of electrochemical sensors brings a fresh approach to low-cost device development.
Keywords: Acid treatment;; Electrochemical sensors;; Low-cost; Renewable carbon;; Surface modification;